La Apología de Platón o la defensa del mal ciudadano - Benéitez, Javier (Foro Interno, 2008)
By exploring how classical Athens dealt with the problems that arose between its civic ethos and the individual tendencies of its citizens, we can better understand how this city grappled with the challenges that individual opinions can pose for civic cohesion. Our analysis portrays this clash in the figure of Socrates, as depicted in Plato’s Apology. Specifically, the way in which Socrates behaved in the courtroom highlights certain features of individual attitudes in the sphere of the Athenian ethos. This article seeks to offer a deeper understanding of ancient political life in the Athenian polis, and also provide a reflection on the complex relationship between the individual and the State.
Keywords: Bad citizenship; Democracy; Self-interested citizen; Socrates; Plato’s Apology of Socrates